1982
DOI: 10.1007/bf00542540
|View full text |Cite
|
Sign up to set email alerts
|

The influence of theophylline on maximal response to salbutamol in severe chronic obstructive pulmonary disease

Abstract: We have previously shown that inhaled salbutamol further increases the bronchodilator response after the maximum effect of theophylline has been obtained in patients with severe chronic bronchitis. We now report the results of adding maximally effective doses of theophylline to the maximum response obtainable from salbutamol in ten of these patients. We constructed dose response curves to ensure maximum possible effect from salbutamol. Response plateaus (in nine out of ten patients) were achieved with cumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…A positive correlation between maximum bronchodilator response and the dose of β 2 -adrenoceptor agonist used is not always observed. However, a 50% increase in FEV1 is obtained with 400 µg salbutamol and an increase in the dose of this agent may produce further increases in FEV1 [30]. In any case, the results of this study apparently refute the assertion that airway obstruction secondary to increased vagal tone, and is the only dominant reversible element in patients suffering from COPD.…”
Section: Discussioncontrasting
confidence: 51%
“…A positive correlation between maximum bronchodilator response and the dose of β 2 -adrenoceptor agonist used is not always observed. However, a 50% increase in FEV1 is obtained with 400 µg salbutamol and an increase in the dose of this agent may produce further increases in FEV1 [30]. In any case, the results of this study apparently refute the assertion that airway obstruction secondary to increased vagal tone, and is the only dominant reversible element in patients suffering from COPD.…”
Section: Discussioncontrasting
confidence: 51%
“…Since methylxanthines have multiple side effects with considerable potential for serious toxicity, whereas inhaled bronchodilators are generally safe, a more relevant question is whether theophylline provides any additional benefit in patients already receiving inhaled bronchodilators at optimal dosage. Studies have shown that some patients (40-50%) [59,60] display additional bronchodilatation (increase in FEV 1 of 32% or 0.22 D [59] when theophylline is added to large doses of inhaled bronchodilator. Whether this additional bronchodilatation translates into improved exer-oxygen.…”
Section: (C) Methylxanthinesmentioning
confidence: 99%
“…If they are adequately informed and closely followed, a trial of theophylline in the mid to slightly lower therapeutic range (12)(13)(14)(15) jg/ml) is important for those in whom dyspnoea gradually assumes total dominion over their lives. (2) Severe asthmatic patients in whom oral corticosteroids are being used or may be otherwise necessary.…”
Section: Clear Indicationsmentioning
confidence: 99%